Triazol-substituted titanocenes by strain-driven 1,3-dipolar cycloadditions - Gansäuer, Andreas; Okkel, Andreas; Schwach, Lukas; Wagner, Laura; Selig, Anja; Prokop, Aram (Beilstein Journal of Organic Chemistry, 2014)
An operationally simple, convenient, and mild strategy for the synthesis of triazole-substituted titanocenes via strain-driven 1,3-dipolar cycloadditions between azide-functionalized titanocenes and cyclooctyne has been developed. It features the first synthesis of titanocenes containing azide groups. These compounds constitute ‘second-generation’ functionalized titanocene building blocks for further synthetic elaboration. Our synthesis is modular and large numbers of the complexes can in principle be prepared in short periods of time. Some of the triazole-substituted titanocenes display high cyctotoxic activity against BJAB cells. Comparison of the most active complexes allows the identification of structural features essential for biological activity.
Keywords: azides; click-chemistry; cycloadditions; cytotoxicity; titanocenes

(untitled) - Buettner, K. M.; Valentine, A. M. (Chem. Rev., 2012)

(untitled) - Hartinger, C. G.; Metzler-Nolte, N.; Dyson, P. J. (Organometallics, 2012)

(untitled) - Tshuva, E. Y.; Ashenhurst, J. A. (Eur. J. Inorg. Chem., 2009)

(untitled) - Strohfeldt, K.; Tacke, M. (Chem. Soc. Rev., 2008)

(untitled) - Köpf-Maier, P.; Köpf, H. (Chem. Rev., 1987)

(untitled) - Sirignano, E.; Saturnino, C.; Botta, A.; Sinicropi, M. S.; Caruso, A.; Pisano, A.; Lappano, R.; Maggiolini, M.; Longo, P. (Bioorg. Med. Chem. Lett., 2013)

(untitled) - Schur, J.; Manna, C. M.; Deally, A.; Köster, R. W.; Tacke, M.; Tshuva, E. Y.; Ott, I. (Chem. Commun., 2013)

(untitled) - Kater, L.; Claffey, J.; Hogan, M.; Jesse, P.; Kater, B.; Strauss, S.; Tacke, M.; Prokop, A. (Toxicol. in Vitro, 2012)

(untitled) - González-Pantoja, J. F.; Stern, M.; Jarzecki, A. A.; Royo, E.; Robles-Escajeda, E.; Varela-Ramírez, A.; Aguilera, R. J.; Contel, M. (Inorg. Chem., 2011)

(untitled) - Gao, L. M.; Vera, J. L.; Matt, J.; Meléndez, E. (J. Biol. Inorg. Chem., 2010)

(untitled) - Carter, M. B.; Schiøtt, B.; Gutiérrez, A.; Buchwald, S. L. (J. Am. Chem. Soc., 1994)

(untitled) - Pohlki, F.; Doye, S. (Angew. Chem., Int. Ed., 2001)

(untitled) - Cuerva, J. M.; Justicia, J.; Oller-López, J. L.; Oltra, J. E. (Top. Curr. Chem., 2006)

(untitled) - Gansäuer, A.; Justicia, J.; Fan, C.-A.; Worgull, D.; Piestert, F. (Top. Curr. Chem., 2007)

(untitled) - Gansäuer, A.; Fleckhaus, A.; Lafont, M. A.; Okkel, A.; Kotsis, K.; Anoop, A.; Neese, F. (J. Am. Chem. Soc., 2009)

(untitled) - Streuff, J.; Feurer, M.; Bichovski, P.; Frey, G.; Gellrich, U. (Angew. Chem., Int. Ed., 2012)

(untitled) - Dastidar, P. (Chem. Soc. Rev., 2008)

(untitled) - Piepenbrok, M.-O. M.; Lloyd, G. O.; Clarke, N.; Steed, J. W. (Chem. Rev., 2010)

(untitled) - Klawonn, T.; Gansäuer, A.; Winkler, I.; Lauterbach, T.; Franke, D.; Nolte, R. J. M.; Feiters, M. C.; Börner, H.; Hentschel, J.; Dötz, K. H. (Chem. Commun., 2007)

(untitled) - Gansäuer, A.; Winkler, I.; Klawonn, T.; Nolte, R. J. M.; Feiters, M. C.; Börner, H. G.; Hentschel, J.; Dötz, K. H. (Organometallics, 2009)

(untitled) - Halterman, R. L. (Chem. Rev., 1992)

(untitled) - Qian, Y.; Huang, J.; Bala, M. D.; Lian, B.; Zhang, H.; Zhang, H. (Chem. Rev., 2003)

(untitled) - Gansäuer, A.; Franke, D.; Lauterbach, T.; Nieger, M. (J. Am. Chem. Soc., 2005)

(untitled) - Gansäuer, A.; Winkler, I.; Worgull, D.; Franke, D.; Lauterbach, T.; Okkel, A.; Nieger, M. (Organometallics, 2008)

(untitled) - Gansäuer, A.; Okkel, A.; Worgull, D.; Schnakenburg, G. (Organometallics, 2010)

(untitled) - Gansäuer, A.; Winkler, I.; Worgull, D.; Lauterbach, T.; Franke, D.; Selig, A.; Wagner, L.; Prokop, A. (Chem.–Eur. J., 2008)

(untitled) - Gansäuer, A.; Lauterbach, T.; Geich-Gimbel, D. (Chem.–Eur. J., 2004)

(untitled) - Friedrich, J.; Dolg, M.; Gansäuer, A.; Geich-Gimbel, D.; Lauterbach, T. (J. Am. Chem. Soc., 2005)

(untitled) - Friedrich, J.; Walczak, K.; Dolg, M.; Piestert, F.; Lauterbach, T.; Worgull, D.; Gansäuer, A. (J. Am. Chem. Soc., 2008)

(untitled) - Gansäuer, A.; Worgull, D.; Knebel, K.; Huth, I.; Schnakenburg, G. (Angew. Chem., Int. Ed., 2009)

(untitled) - Gansäuer, A.; Knebel, K.; Kube, C.; van Gastel, M.; Cangönül, A.; Daasbjerg, K.; Hangele, T.; Hülsen, M.; Dolg, M.; Friedrich, J. (Chem.–Eur. J., 2012)

(untitled) - Jiménez, T.; Morcillo, S. P.; Martín-Lasanta, A.; Collado-Sanz, D.; Cárdenas, D. J.; Gansäuer, A.; Justicia, J.; Cuerva, J. M. (Chem.–Eur. J., 2012)

(untitled) - Morcillo, S. P.; Martinez-Peragón, Á.; Jakoby, V.; Mota, A. J.; Kube, C.; Justicia, J.; Cuerva, J. M.; Gansäuer, A. (Chem. Commun., 2014)

(untitled) - Sletten, E. M.; Bertozzi, C. R. (Angew. Chem., Int. Ed., 2009)

(untitled) - Jewett, J. C.; Bertozzi, C. R. (Chem. Soc. Rev., 2010)

(untitled) - Wittig, G.; Krebs, A. (Chem. Ber., 1961)

(untitled) - Agard, N. J.; Prescher, J. A.; Bertozzi, C. R. (J. Am. Chem. Soc., 2004)

(untitled) - Gordon, C. G.; Mackey, J. L.; Jewett, J. C.; Sletten, E. M.; Houk, K. N.; Bertozzi, C. R. (J. Am. Chem. Soc., 2012)

(untitled) - Hudak, J. E.; Barfield, R. M.; de Hart, G. W.; Grob, P.; Nogales, E.; Bertozzi, C. R.; Rabuka, D. (Angew. Chem., Int. Ed., 2012)

(untitled) - de Almeida, G.; Sletten, E. M.; Nakamura, H.; Palaniappan, K. K.; Bertozzi, C. R. (Angew. Chem., Int. Ed., 2012)

(untitled) - Tornøe, C. W.; Christensen, C.; Meldal, M. (J. Org. Chem., 2002)

(untitled) - Rostovtsev, V. V.; Green, L. G.; Fokin, V. V.; Sharpless, K. B. (Angew. Chem., Int. Ed., 2002)

(untitled) - Zhang, L.; Chen, X.; Xue, P.; Sun, H. H. Y.; Williams, I. D.; Sharpless, K. B.; Fokin, V. V.; Jia, G. (J. Am. Chem. Soc., 2005)

(untitled) - Zagerman, J.; Deally, A.; Metzler-Nolte, N.; Müller-Bunz, H.; Wallis, D.; Tacke, M. (Polyhedron, 2011)

(untitled) - Golobov, Y. M.; Kasukhin, L. F. (Tetrahedron, 1992)

(untitled) - Köhn, M.; Breinbauer, R. (Angew. Chem., Int. Ed., 2004)

(untitled) - Bantel, H.; Engels, I. H.; Völter, W.; Schulze-Osthoff, K.; Wesselborg, S. (Cancer Res., 1999)

(untitled) - Klener, P., Jr; Anděra, L.; Klener, P.; Nečas, E.; Živný, J. (Folia Biol. (Prague, Czech Repub.), 2006)

(untitled) - Meiler, J.; Schuler, M. (Curr. Drug Targets, 2006)

(untitled) - Wieder, T.; Prokop, A.; Bagci, B.; Essmann, F.; Bernicke, D.; Schulze-Osthoff, K.; Dörken, B.; Schmalz, H.-G.; Daniel, P. T.; Henze, G. (Leukemia, 2001)

(untitled) - Diller, R. A.; Riepl, H. M.; Rose, O.; Frias, C.; Henze, G.; Prokop, A. (Planta Med., 2007)

(untitled) - Prokop, A.; Wrasidlo, W.; Lode, H.; Herold, R.; Lang, F.; Henze, G.; Dörken, B.; Wieder, T.; Daniel, P. T. (Oncogene, 2003)

(untitled) - Rudner, J.; Lepple-Wienhues, A.; Budach, W.; Berschauer, J.; Friedrich, B.; Wesselborg, S.; Schulze-Osthoff, K.; Belka, C. (J. Cell Sci., 2001)

(untitled) - Gansäuer, A.; Fan, C.-A.; Keller, F.; Karbaum, P. (Chem.–Eur. J., 2007)

(untitled) - Gansäuer, A.; Shi, L.; Otte, M. (J. Am. Chem. Soc., 2010)

(untitled) - Gansäuer, A.; Pierobon, M. (Synlett, 2000)

(untitled) - Gansäuer, A.; Pierobon, M.; Bluhm, H. (Synthesis, 2001)

(untitled) - Barrero, A. F.; Quilez del Moral, J. F.; Sánchez, E. M.; Arteaga, J. F. (Eur. J. Org. Chem., 2006)